Characteristics of combined carbon dioxide reforming with partial oxidation of methane to produce hydrogen in the membrane reactor. (27th October 2016) - Yan, Yunfei; Wu, Gange; Zhang, Li; Wang, Xin; Li, Lixian; Yang, Zhongqing; Ran, Jing
Summary: Thermodynamic equilibrium constant method and mathematical model are used to analyze the investigating effects of temperature, α[oxygen‐methane molar ratio] and β [carbon dioxide‐methane molar ratio] on characteristics of oxidative CO2 reforming of methane reaction over Ni/Al2 O3 catalysts to produce hydrogen in the membrane reactor. While keeping temperature at 1100 K, the membrane reactor is no longer useful to separate hydrogen when α > 0.6 for hydrogen in reaction side is no longer to permeate side. When increasing β, the methane conversion goes up firstly until the β is 1.3, which is higher than the inflection point at 1.1 in the model prediction. The hydrogen yield peaks at β = 0.5 in permeate side. Increasing the temperature or reducing the β will cause the molar ratio of H2 /CO increase. However, changing α has no significant effect on adjusting the molar ratio of H2 /CO. By establishing equilibrium reaction model, the system performance can be accurately predicted. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In the article 'Characteristics of Combined CO2 Reforming with Partial Oxidation of CH4 to Produce H2 in the Membrane Reactor', Yunfei Yan *, Gange Wu, Li Zhang, and so on combined thermodynamic equilibrium constant method and mathematical model to analyze the investigating effects of temperature, α[O2 /CH4 ] and β [CO2 /CH4 ] on characteristics of oxidative CO2 reforming of methane reaction over Ni/Al2 O3 catalysts to produce hydrogen in the membrane reactor.